Pink bollworm Pectinophora gossypiella (Saunders), a destructive pest of cotton: A review - Bhute, N K; Patil, C S; Deshmukh, K V; Wagh, R S; Medhe, N K (Indian Journal of Plant Protection, 2025)
Cotton, the important cash crop, globally known as “King of Fibre” offers an important natural fabric material to the world has been a point of fascination. Since it is grown as major cash crop in India, appears to have been the center of an important cotton industry as early as 1500 BC. Besides serving as a source of natural fiber, it is also an oilseed crop, providing raw material to the oil and textile industries, playing dominant role in the economic and social status of the people. Amongst the various factors responsible for low yields, the losses due to pests assume significant importance as cotton crop is a heaven for insects. A total of 1326 species of insects have been recorded on cotton throughout the world. The pest spectrum of cotton crop is quite complex comprising of several species of the insects. However, main losses in cotton production are due to its susceptibility to about 162 species of insect pests. The sucking pests and bollworm complex account for a considerable yield loss up to 36.2 per cent. Chemical insecticides, are being used extensively for control of these insect pests. After the introduction of Bt cotton the use of pesticides minimized and the problem of bollworms was solved, but from last few years, pink bollworm has developed resistance against Bt toxins. Worldwide, pink bollworm has become economically the most notorious pest of cotton. Among the bollworms, pink bollworm poses greater threat to the cotton in recent past and has known to cause loss in normal opening of bolls, loss in oil content, seed cotton yield and damage locules. The authors tried here to collect the information about its distribution and origin, seasonal incidence, life history, nature of damage, symptoms, different management tools including IPM strategies.